Analisis Pengaruh Perlakuan Kimia terhadap Morfologi dan Gugus Fungsional Serat Sisal - Purwanto Purwanto; Arif Rakhman Suharso; Fajar Sari Kurniawan (Newton-Maxwell Journal of Physics, 2021)
Morphological and functional group analysis was carried out to study the appearance of micro and molecular structures contained in sisal fibers before and after chemical scouring and bleaching treatment. The scouring and bleaching process lasts for 1 hour with continuous stirring using a magnetic stirrer. Scouring was carried out with 6% NaOH solution while Bleaching was carried out with a solution of 10 g / L NaOH and 100 ml / L H2O2. Scanning Electron Microscopy (SEM) was used to identify the surface appearance and diameter of the fibers before and after the scouring and bleaching processes. Fourier transform infrared (FTIR) spectroscopy is used to identify functional groups in fibers. The Bleaching  process shows that the functional groups identified are the same as those of pure cellulose or alpha cellulose, namely -CH2, C-O, C = C, -CH3, C?C, and -OH, C-H. Sisal fibers with a diameter between 100 - 150 µm break down (fibrillate) into smaller fibers after the scouring (diameter: ?12 µm) and bleaching (diameter: ?7µm) processes. Thus, scouring and bleaching have caused significant changes in the morphological and microstructure of the fiber surface and also the functional groups that the sisal fiber has after the bleaching process is the same as pure fiber.